2012
DOI: 10.1007/s00005-012-0207-9
|View full text |Cite
|
Sign up to set email alerts
|

Associated Immunological Disorders and Cellular Immune Dysfunction in Thymoma: A Study of 87 Cases from Thailand

Abstract: Several immune disorders are often associated with thymoma. The aim of this study was to analyze the correlation between clinicopathological features of Thai patients with thymoma and concomitant immune-mediated diseases. Medical records of 87 patients diagnosed with thymoma during a 10-year period were retrospectively reviewed. Peripheral blood T cell subsets along with cytokine responses in 15 thymoma patients and 15 healthy controls were comparatively analyzed. The results demonstrated that thymoma type AB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
13
0
1
Order By: Relevance
“…Although patients with thymoma B2 may, in rare cases, exhibit hypogammaglobulinemia and cellular immune dysfunction ( 11 ), this patient was considered immunocompetent because his medical history and follow-up after this infection did not show any indication of immune deficiency. The change in neutrophil count during acute infection is intriguing because neutrophils have been shown to serve as a reservoir for WNV replication during early infection and to contribute to viral clearance at a later stage of illness ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with thymoma B2 may, in rare cases, exhibit hypogammaglobulinemia and cellular immune dysfunction ( 11 ), this patient was considered immunocompetent because his medical history and follow-up after this infection did not show any indication of immune deficiency. The change in neutrophil count during acute infection is intriguing because neutrophils have been shown to serve as a reservoir for WNV replication during early infection and to contribute to viral clearance at a later stage of illness ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Se han publicado múltiples fenómenos autoinmunes en relación con timoma, fundamentalmente en relación con miastenia gravis, pero también polimiositis, lupus, artritis reumatoide, tiroiditis, Sjogren, hepatitis autoinmune, enfermedad celiaca, pén go…y en ocasiones solapándose unas a otras 3 dejando entrever por tanto una relación inmunopatológica La diferenciación histopatológica (clasi cación Who) parece tener relación con la asociación a autoinmunidad siendo el fenotipo B2 el más frecuentemente asociado 2 . La asociación con artritis reumatoide es poco frecuente con tan solo 3 casos descritos en literatura, uno asociado a tiroiditis de Hashimoto 4 y dos de ellos asociados a la toma de fármacos inmunosupresores y aparición de timoma en dicho contexto 5,6 .…”
Section: Caso Clínicounclassified
“…Thymoma is a mediastinal tumor originating from the thymus epithelial cells and accounting for approximately 25% of mediastinal tumors . Approximately 30% of patients with thymoma also have myasthenia gravis (MG) . Recently, studies have suggested that thymoma with autoimmune disorders is likely mediated by the dysfunction in central tolerance and immunoregulation .…”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately 30% of patients with thymoma also have myasthenia gravis (MG). 2 Recently, studies have suggested that thymoma with autoimmune disorders is likely mediated by the dysfunction in central tolerance and immunoregulation. 3 However, the precise mechanisms underlying the process of thymoma-related disorders have not been clarified.…”
Section: Introductionmentioning
confidence: 99%